The Symbiotic Continuum Within Ticks: Opportunities for Disease Control - Hussain, Sabir; Perveen, Nighat; Hussain, Abrar; Song, Baolin; Aziz, Muhammad Umair; Zeb, Jehan; Li, Jun; George, David; Cabezas-Cruz, Alejandro; Sparagano, Olivier (Frontiers in Microbiology, 2022)
Among blood-sucking arthropods, ticks are recognized as being of prime global importance because of their role as vectors of pathogens affecting human and animal health. Ticks carry a variety of pathogenic, commensal, and symbiotic microorganisms. For the latter, studies are available concerning the detection of endosymbionts, but their role in the physiology and ecology of ticks remains largely unexplored. This review paper focuses on tick endosymbionts of the genera Coxiella, Rickettsia, Francisella, Midichloria, and Wolbachia, and their impact on ticks and tick-pathogen interactions that drive disease risk. Tick endosymbionts can affect tick physiology by influencing nutritional adaptation, fitness, and immunity. Further, symbionts may influence disease ecology, as they interact with tick-borne pathogens and can facilitate or compete with pathogen development within the vector tissues. Rickettsial symbionts are frequently found in ticks of the genera of Ixodes, Amblyomma, and Dermacentor with relatively lower occurrence in Rhipicephalus, Haemaphysalis, and Hyalomma ticks, while Coxiella-like endosymbionts (CLEs) were reported infecting almost all tick species tested. Francisella-like endosymbionts (FLEs) have been identified in tick genera such as Dermacentor, Amblyomma, Ornithodoros, Ixodes, and Hyalomma, whereas Wolbachia sp. has been detected in Ixodes, Amblyomma, Hyalomma, and Rhipicephalus tick genera. Notably, CLEs and FLEs are obligate endosymbionts essential for tick survival and development through the life cycle. American dog ticks showed greater motility when infected with Rickettsia, indirectly influencing infection risk, providing evidence of a relationship between tick endosymbionts and tick-vectored pathogens. The widespread occurrence of endosymbionts across the tick phylogeny and evidence of their functional roles in ticks and interference with tick-borne pathogens suggests a significant contribution to tick evolution and/or vector competence. We currently understand relatively little on how these endosymbionts influence tick parasitism, vector capacity, pathogen transmission and colonization, and ultimately on how they influence tick-borne disease dynamics. Filling this knowledge gap represents a major challenge for future research.